Information gain XGBoost for feature selection in structural health monitoring of bridges - Rosa, Heitor Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Recent efforts in structural health monitoring (SHM) have focused on strategies utilizing statistical pattern recognition, where extracting damage-sensitive features from raw data is critical. The large volume of features generated from multiple sensors and signals often includes irrelevant data and noise, challenging accurate damage detection. Selecting the most informative features is paramount to transit bridge SHM from research to practice. This work contributes to the bridge SHM field by introducing a decision tree-based information gain approach to automate feature selection, enhancing sensitivity to damage. The study uses data from the Z24 Bridge, analyzing its undamaged state and eight different damaged state conditions. Features were extracted using frequency- and time-domain techniques. The proposed approach was compared with two other approaches, based on permutation importance and F- statistics, demonstrating a superior trade-off in classification performance, identifying a smaller and more effective subset of features. An XGBoost classifier was used to overcome the challenges of missing data inherent to field monitoring. The time-domain features were enhanced for real-world bridge applications and proposed as an alternative to traditional frequency-domainfeatures. Additionally, a sensor-level sensitivity analysis revealed new possibilities for applying tree-based algorithms in SHM sensor analysis, underscoring the practical impact of this method even for damage localization.

Os esforços recentes na monitorização da saúde estrutural (SHM) concentraram-se em estratégias que utilizam reconhecimento de padrões estatísticos, onde a extração de features sensíveis a danos de dados brutos é crítico. O grande volume de features gerados a partir de múltiplos sensores e sinais frequentemente inseridos inclui dados e ruídos irrelevantes, desafiando a detecção precisa de danos. Selecionando o mais features informativos são fundamentais para fazer a ponte entre o SHM da pesquisa e a prática. Este trabalho contribui para o campo de monitoramento de pontes introduzindo um ganho de informação baseado em árvore de decisão abordagem para automatizar a seleção de features, aumentando a sensibilidade a danos. O estudo usa dados da ponte Z24, analisando seu estado não danificado e oito diferentes condições de estado danificado. As características foram extraídas usando técnicas no domínio da frequência e do tempo. A proposta abordagem foi comparada com duas outras abordagens, com base na importância da permutação e F-statistics, demonstrando um compromisso superior no desempenho da classificação, identificando um menor e um subconjunto de features mais eficaz. Um classificador XGBoost foi usado para superar o desafio grande quantidade de dados faltantes inerentes ao monitoramento de campo. Os features de domínio do tempo foram aprimorados para aplicações de ponte do mundo real e propostas como uma alternativa ao domínio de frequência tradicional características. Além disso, uma análise de sensibilidade ao nível do sensor revelou novas possibilidades de aplicação algoritmos baseados em árvore na análise de sensores SHM, ressaltando o impacto prático deste método mesmo para localização de danos.
Ganho de informação XGBoost para seleção de features no monitoramento da integridade estrutural de pontes
Keywords: Structural health monitoring; Decision tree learning; XGBoost; Feature importance; Information gain